Culture and characterisation of canine mitral valve interstitial and endothelial cells. Issue 1 (April 2015) - Liu, M.-M.; Flanagan, T.C.; Lu, C.-C.; French, A.T.; Argyle, D.J.; Corcoran, B.M.
Highlights: Successful culture and characterisation of valve interstitial and endothelial cells. Identification of CD31 expression and Dil-Ac-LDL uptake as the prime markers for differentiating VECs from VICs. A specific endothelial culture medium for primary VEC cultures enhanced the endothelial properties of the cells. Abstract: Valve interstitial cells (VICs) have an important role in the aetiopathogenesis of myxomatous mitral valve disease (MMVD) in the dog. Furthermore, there is evidence that valve endothelial cells (VECs) also contribute to disease development. In addition to examining native valve tissue to understand MMVD, another strategy is to separately examine VIC and VEC biology under in vitro culture conditions. The aim of this study was to isolate and characterise canine mitral VICs and VECs from normal dog valves using a combination of morphology, immunohistochemistry and reverse transcription PCR (RT-PCR). Canine mitral VECs and VICs were isolated and cultured in vitro. The two cell populations exhibited different morphologies and growth patterns. VECs, but not VICs, expressed the endothelial markers, platelet endothelial cell adhesion molecule (PECAM-1 or CD31) and acetylated low density lipoprotein (Dil-Ac-LDL). Both VECs and VICs expressed vimentin and embryonic non-smooth muscle myosin heavy chain (SMemb), an activated mesenchymal cell marker. The myofibroblast marker, alpha smooth muscle actin (α-SMA), was detected at the mRNA level in both VEC and VIC cultures, but only at the protein level in VIC cultures. The morphological heterogeneity and expression of non-endothelial phenotypic markers in VEC cultures suggested that a mixture of cell types was present, which might be due to cell contamination and/or endothelial–mesenchymal transition (EndoMT). The use of a specific endothelial culture medium for primary VEC cultures enhanced the endothelial properties of the cells and reduced α-SMA and SMemb expression.